PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI IPAS KELAS IV DI SDN MERJOSARI 1 KOTA MALANG - Martha Rengu Teba; Moh. Farid Nurul Anwar; Chusnul Chotimah; Muhamad Rifai (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of Problem-Based Learning emphasizes the ability to solve problems. Students are required to be active in order to grasp the concepts to be applied when solving problems; they must be able to master and explore these concepts on their own; and they are expected to actively ask questions and present arguments through discussion, practice investigative skills, and carry out other steps of the scientific process. This study aims to improve student learning outcomes in the IPAS subject, specifically the “Indonesia’s Rich Culture” unit, through the implementation of the Problem-Based Learning (PBL) model among fourth-grade students at SDN Merjosari 1 in Malang City. This study employed the Classroom Action Research (CAR) method, conducted in two cycles, with each cycle comprising the planning, implementation, observation, and reflection stages. The research subjects consisted of 28 fourth-grade students. Data were collected through observation, learning achievement tests, and documentation, while data analysis employed both quantitative and qualitative descriptive analysis.. . The results of the study show that the implementation of the PBL model was able to significantly improve student learning outcomes. Students’ average scores increased from 58.85 in the pre-cycle to 75.50 in Cycle I and 93.14 in Cycle II. The percentage of students meeting learning standards also increased from 28.57% in the pre-cycle to 67.85% in Cycle I and reached 92.85% in Cycle II. In addition to improving learning outcomes, the PBL model also encouraged students to be more active in critical thinking, discussion, problem-solving, and collaboration during the learning process. Thus, the implementation of the Problem-Based Learning model has proven effective in improving student learning outcomes on the “Indonesia’s Rich Culture” curriculum in fourth grade at SDN Merjosari 1 in Malang City.